Engineered Polymeric Carbon Nitride Additive for Energy Storage Materials: A Review. (26th July 2021) - Wang, Zhonghao; Jin, Bingjun; Peng, Jun; Su, Wan; Zhang, Kan; Hu, Xun; Wang, Guannan; Park, Jong Hyeok
Abstract: The ever‐increasing demands for high energy density electronics have motivated research on exploring new types of electrode materials featuring mechanical flexibility and electrical storage capability. Of these, polymeric carbon nitride (PCN) has been increasingly studied in regard to electrical energy storage (EES) because of its abundant pyridinic N content, which is beneficial for enhancing electrochemical performance. However, state‐of‐the‐art PCN‐based electrode materials for EES are still far from industrial requirements. Herein, the current status of PCN‐based materials in batteries and supercapacitors (SCs) is primarily discussed. A particular emphasis is placed on the PCN processing into composite electrode materials, including the defect engineering of pristine PCN and its coupling with other conductive materials to develop heterojunction nanostructures, which is essential for developing highly efficient electrode materials. Moreover, the direct pyrolysis of PCN into N‐doped graphene with a tunable N content is introduced and achieves remarkable energy storage performance with superior electronic conductivity. Furthermore, the energy storage mechanisms for batteries and SCs are also highlighted to reveal structure–performance relationship. Finally, this comprehensive review outlines the remaining challenges and strategies for future improvements in PCN‐based materials in this emerging field. This review will provide inspiration on developing future PCN‐based materials for EES. Abstract : Polymeric carbon nitride (PCN) has been increasingly studied in energy storage fields. Herein, the recent developments on the constructions and applications of PCN‐based nanocomposites in various types of batteries and supercapacitors are summarized with a focus on engineering PCN into electrode materials, accompanied by providing mechanism insights into the effects of PCN on enhancing energy storage capability.